(untitled) (Mustansiria Dental Journal, 2018)
The aim was to determine the level of serum, saliva and erythrocyte membrane sialic acid in rheumatoid arthritis patients. Fifty subjects were incorporated in this study, 25 were rheumatoid arthritis patients with mean age 34.6 ± 7.5 years, the other 25 subjects were healthy control with no signs and symptoms of any systemic disease, the mean age was 33.88 ± 6.0. Five ml of blood with 5 ml of unstimulated whole saliva was taken from each subject. After centrifugation of both blood and saliva, the supernatant of saliva and serum was isolated and the red blood cells were used to prepare erythrocyte membrane for the determination of sialic acid. The results revealed that the mean serum sialic acid of rheumatoid arthritis patients was 0.932 ± 0.317, the mean saliva sialic acid was 0.141 ± 0.005 and the mean erythrocyte membrane sialic acid was 0.145 ± 0.035 statistically using t-test the results showed that the mean serum, saliva and erythrocyte membrane sialic acid was significantly higher in rheumatoid arthritis group than that in the control. Significant correlation has been found between serum and saliva sialic acid in both the control and rheumatoid arthritis patients. The elevation of sialic acid in serum, saliva and erythrocyte membrane in rheumatoid arthritis patients indicate that sialic acid considered as an important inflammatory marker for determination the activity of the disease. The significant correlation between serum and saliva sialic acid indicate the importance of saliva to be used in different investigations